Chitosan/hesperidin nanoparticles formulation: a promising approach against ethanol-induced gastric ulcers via Sirt1/FOXO1/PGC-1α/HO-1 pathway - Alamoudi, Jawaher Abdullah; El-Masry, Thanaa A.; El-Nagar, Maysa M. F.; El Zahaby, Enas I.; Elmorshedy, Kadreya E.; Gaballa, Mohamed M. S.; Alshawwa, Samar Zuhair; Alsunbul, Maha; Alharthi, Sitah; Ibrahim, Hanaa A. (Frontiers in Pharmacology, 2024)
Hesperidin (Hes) protects different organs from damage by acting as a potent antioxidant and anti-inflammatory. This study aims to evaluate the gastroprotective effects of free hesperidin and its chitosan nanoparticles (HNPs) against ethanol-induced gastric ulcers in rats, hypothesizing that HNPs will enhance bioavailability and therapeutic efficacy due to improved solubility and targeted delivery. HNPs were synthesized via ion gelation and characterized using TEM, SEM, and zeta potential analyses. Key assessments included gastric acidity, histological analysis, and markers of inflammation, oxidative stress, and apoptosis. HNPs significantly decreased gastric acidity, reduced inflammatory and apoptotic markers, and enhanced antioxidant enzyme activities compared to free hesperidin and esomeprazole. Furthermore, Sirt-1, PGC-1α, HO-1, and FOXO1 gene expression were also evaluated. HNPs raised Sirt-1, PGC-1α, HO-1, and downregulated FOXO1, and they suppressed the activities of NF-κB p65, COX-2, IL-1β, CD86, FOXO1 P53, and caspase-3 and increased Sirt-1 activity. HNPs treatment notably restored antioxidant enzyme activity, reduced oxidative stress and inflammatory markers, and improved histological outcomes more effectively than free hesperidin and esomeprazole. These results indicate that chitosan nanoparticles significantly enhance the gastroprotective effects of hesperidin against ethanol-induced gastric ulcers, potentially offering a more effective therapeutic strategy. Further research should explore the clinical applications of HNPs in human subjects.